Digestive, cognitive and hedonic responses to a meal. Issue 3 (3rd January 2015) - Malagelada, C.; Accarino, A.; Molne, L.; Mendez, S.; Campos, E.; Gonzalez, A.; Malagelada, J. R.; Azpiroz, F.
Abstract Background Gut dysfunctions may be associated to digestive symptoms. We hypothesized that the gut can also originate pleasant sensations, and wished to demonstrate the hedonic component of the digestive response to a meal. Methods Healthy subjects (n = 42) were evaluated during basal fasting conditions and during experimentally induced fullness sensation (either by gastric distension or duodenal nutrient infusion). In each set of studies, a 240 mL test meal (12 kcal broth) and water, as inert control meal, were administered on separate days in a randomized, cross‐over design. Gastric accommodation, the cognitive response and the hedonic dimension (both by 10 score scales) were measured 9 min before and 60 min after the meal. Key Results In basal conditions, the test meal induced a significantly greater gastric relaxation than the control meal (166 ± 28 mL isotonic volume increase 67 ± 14 mL; p = 0.002). Both meals induced epigastric fullness (3.8 ± 0.7 score and 3.2 ± 0.8 score, respectively; p = 0.740), but contrary to the inert meal, with the active meal this conscious sensation had a pleasant dimension (digestive comfort increase by 1.3 ± 0.6 score with active meal vs −1.1 ± 0.6 decrease with inert meal; p = 0.015). Experimentally induced fullness was associated to a decrease in digestive well‐being or abdominal discomfort, which improved only after the active meal but not the inert meal. Conclusions & Inferences When appropriate conditions are met, the response to a meal includes a hedonic dimension involving pleasant sensation of digestive well‐being.